PENGEMBANGAN PERANGKAT PEMBELAJARAN IPS DENGAN PENDEKATAN KONTEKSTUAL BERBANTUAN PETA PIKIRAN - Sugiarti, Iis Yeni (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2017)
The background of the problem in conducting this research is the awareness of contextual approach need to learning based on the fact that most learners are not able to connect the social studies material and the use of it in real life. The purpose of this research is to develop the design of teaching and learning administrations with a contextual approach to social studies aided by mind mapping that fulfills the valid criteria according to the experts, effective and practical of the use. The research method used in this research is research and development, with reference to the model of Plomp including 1)Preliminary Investigation, 2)Design, 3)Realization/Construction, and  4)Test, Evaluation, and Revision. This research is products such as teacher book and students book. The result of this research is: 1)The learning model is designed based on the color and images in the mind map that has its own meaning and closely related to the environment. 2)Social studies with contextual approach assisted map mind is valid with an average of 3.18 validation very good category. 3)Social Studies with contextual approach assisted map mind is effective with an average of 83 leaderboards learning in line with the classical > leaderboard KKM 75. This means that 18 students (78%) meet the value of KKM and 5 students (21%). 4)Social studies with contextual approach assisted map mind is practical with response percentage gain teachers 77,08% and the response of the students 77,22% with a good category. The implementation of this learning, students can instill a caring attitude to the environment.